Forest Ecosystem Service Valuation: A Case of the Kalika Community Forest, Dhading, Central Nepal - Dhungana, Ajad; Deshar, Rashila (Journal of Forests, 2019)
The mid hill of Nepal is also known as the hub of community forestry and Dhading district alone has 681. Valuating ecosystem goods and services is expected to raise public attention to their importance and may trigger support for a suitable conservation strategy. This paper assesses how the community forest ecosystem functioning connected to human wellbeing and what is their monetary value. To answer these questions Kalika community forest of Dhading district, central Nepal was selected since it was rewarded by DFO as the best CFUG in Dhading in 2014. This study presents the results of an attempt to estimate the economic value of goods and service provided by the community forest. Market price method was used for estimation of provisioning goods, productivity method for supporting services, religious value through donation collection from the temple as cultural services and avoided damage cost for the regulating services and secondary data from the community forestry operational plan provided by DFO was also used for the estimation of provisioning goods. The economic value from the ecosystem functioning of the forest was approximate $441,739 per year with an average of $2265 per hector per year. The value of carbon sequestration was estimated high as $1342 per hector per year and the economic value of the cultural services was very low as compared to other but have a greater role in forest conservation. At last this study discusses the importance of outcome for sustainable forest management strategy and suggests some way forward.